Isbah in Malaysia: preventing vices and immoralities - Wan Muhammad, Ramizah (Bangladesh Institute of Islamic Thought (BIIT), 2016)
This paper analyses the role of the ×isbah institution, the Religious Enforcement Division at the State Religious Department in Malaysia, in curbing immoral activities as well as other contemptible acts according to sharÊ’ah. In the division, there are Religious Enforcement Officers who warn the potential offenders and also arrest anyone for the violation of rules incorporated in the Islamic enactments. The objectives of establishing the division as well as the department are to protect the sanctity of Islam as a way of life and to prevent Muslims from immoral activities. Each state in Malaysia has its own Department. These Departments carry different names but they perform similar functions of prohibiting vice and preventing ma’Îiah i.e. transgression. Based upon documentary evidence and court cases, this paper highlights the current developments in the Division and the challenges it faces in protecting Muslim’s faith in Malaysia.